Human Enhancement Technologies: Future Outlook and Challenges - Ozcan Saritas (Foresight and STI Governance)
Relations between the human and hi-tech worlds, even until recently considered the subject of science fiction, are taking a more real shape and becoming the focus of expert discussions. Some specialists suggest that in the future machines can become the principal creator of new technologies and race far ahead of humanity. However, emerging technologies for human enhancement offer new possibilities for humans to remain competitive against machines and to acquire more advanced physical and mental capacities. These techniques are interdisciplinary, drawing primarily on advances in medicine, pharmacology, nutrition, mobile communications, neuroscience and cognitive sciences.